Effects of high CO2 treatment on green-ripening and peel senescence in banana and plantain fruits - Mu-bo SONG; Lu-ping TANG; Xue-lian ZHANG; Mei BAI; Xue-qun PANG; Zhao-qi ZHANG (Journal of Integrative Agriculture, 2015)
Banana fruit (Musa, AAA group, cv. Brazil) peel fails to fully degreen but the pulp ripens normally at temperatures above 24°C. This abnormal ripening, known as green-ripening, does not occur in plantains (Musa, ABB group, cv. Dajiao). Based on the fact that un-completely yellowing was also observed for bananas in poorly ventilated atmospheres, in the present study, the effect of high CO2 with regular O2 (21%) on banana ripening was investigated along with that on plantains at 20°C. The results showed that high CO2 conferred different effects on the color changing of bananas and plantains. After 6 d ripening in 20% CO2, plantains fully yellowed, while bananas retained high chlorophyll content and stayed green. In contrast to the differentiated color changing patterns, the patterns of the softening, starch degradation and soluble sugar accumulation in the pulp of 20% CO2 treated bananas and plantains displayed similarly as the patterns in the fruits ripening in regular air, indicating that the pulp ripening was not inhibited by 20% CO2, and the abnormal ripening of bananas in 20% CO2 can be considered as green ripening. Similar expression levels of chlorophyll degradation related genes, SGR, NYC and PaO, were detected in the peel of the control and treated fruits, indicating that the repressed degreening in 20% CO2 treated bananas was not due to the down-regulation of the chlorophyll degradation related genes. Compared to the effect on plantains, 20% CO2 treatment delayed the decline in the chlorophyll florescence (Fv/Fm) values and in the mRNA levels of a gene coding small subunit of Rubisco (SSU), and postponed the disruption of the ultrastructure of chloroplast in the peel tissue of bananas, indicating that the senescence of the green cells in the exocarp layer was delayed by 20% CO2, to more extent in bananas than in plantains. High CO2 reduced the ethylene production and the expression of the related biosynthesis gene, ACS, but elevated the respiration rates in both cultivars. The up-regulation of the expression of anaerobic respiration pathway genes, ADH and PDC, might be responsible for the subtle effect of high CO2 on the pulp ripening. Taken together, the atmosphere of high CO2 and regular O2, delayed the senescence of the green cells in the exocarp layer of the banana peel, but conferred no obvious inhibition on the pulp ripening, leading to a distinct green-ripening that was different from the phenomenon induced by high temperatures.